1998
DOI: 10.1063/1.367981
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silicon on the glass forming ability of the Cu47Ti34Zr11Ni8 bulk metallic glass forming alloy during processing of composites

Abstract: Composites of the Cu 47 Ti 34 Zr 11 Ni 8 bulk metallic glass, reinforced with up to 30 vol % SiC particles are synthesized and characterized. Results based on x-ray diffraction, optical microscopy, scanning Auger microscopy, and differential scanning calorimetry ͑DSC͒ are presented. During processing of the composites, a TiC layer forms around the SiC particles and Si diffuses into the Cu 47 Ti 34 Zr 11 Ni 8 matrix stabilizing the supercooled liquid against crystallization. The small Si addition between 0.5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(109 citation statements)
references
References 15 publications
11
96
2
Order By: Relevance
“…[2][3][4] Very recently, the report of ternary Cu 60 Ti 10 Zr 30 and Cu 60 Ti 15 Hf 25 systems, 5,6 exhibiting excellent mechanical properties, has triggered considerable research activity in this area, especially in the microstructure of the ternary systems. [5][6][7][8][9][10][11][12] Inoue et al, 5,6 reported that bulk glassy alloys with a rod diameter of 4 mm can be formed in the ternary Cu 60 Ti 10 Zr 30 and Cu 60 Ti 15 Hf 25 systems.…”
mentioning
confidence: 99%
“…[2][3][4] Very recently, the report of ternary Cu 60 Ti 10 Zr 30 and Cu 60 Ti 15 Hf 25 systems, 5,6 exhibiting excellent mechanical properties, has triggered considerable research activity in this area, especially in the microstructure of the ternary systems. [5][6][7][8][9][10][11][12] Inoue et al, 5,6 reported that bulk glassy alloys with a rod diameter of 4 mm can be formed in the ternary Cu 60 Ti 10 Zr 30 and Cu 60 Ti 15 Hf 25 systems.…”
mentioning
confidence: 99%
“…The addition of Si might help to destabilize some clusters present in the melt, which contain some impurities, such as oxide or carbon, and be favorable to form competing crystallization phase. 21) Si has a small atomic radius of less than 0.12 nm, which would be in favor of large atomic size mismatches and significant disorder in structural topology; consequently, supports the formation of glassy structure during solidification. The minor amount of Si may facilitate the formation of a new local atomic structure, which is favorable to stabilize the supercooled liquid.…”
Section: Resultsmentioning
confidence: 99%
“…% Sn or Si can destabilize the primary crystallized phase in Cu 60 Zr 30 Ti 10 or Cu 47 Ti 34 -Ni 8 Zr 11 melt. 10,13) It is reasonable that Sn and Si might play a similar role in our Cu-based alloys, and therefore the stability of the undercooled liquids is enhanced with the introduction of Sn and Si in Cu 50 Zr 42:5 Ti 7:5 , reflected by the increase in the values of T rg and ÁT x . It is well known that the glass-forming ability is closely related to T rg or ÁT x .…”
Section: Methodsmentioning
confidence: 99%
“…The small Y or Sn addition can stabilize the undercooled liquid of Cu-and Fe-based alloys, and drastically improved the glassforming ability. 10,[12][13][14][15][16] In our detailed investigation of glass formation for ternary Cu-Zr-Ti system, it was found that the BMGs can be formed in a very broad composition range from 45 to 60 at. % Cu, and Cu 50 Zr 42:5 Ti 7:5 is another strong bulk metallic glass former, except for Cu 60 Zr 30 Ti 10 .…”
Section: Introductionmentioning
confidence: 99%